MiR148b is a major coordinator of breast cancer progression in a relapse‐associated microRNA signature by targeting ITGA5, ROCK1, PIK3CA, NRAS, and CSF1. Issue 3 (11th December 2012) - Cimino, Daniela; De Pittà, Cristiano; Orso, Francesca; Zampini, Matteo; Casara, Silvia; Penna, Elisa; Quaglino, Elena; Forni, Marco; Damasco, Christian; Pinatel, Eva; Ponzone, Riccardo; Romualdi, Chiara; et al.
Abstract : Breast cancer is often fatal during its metastatic dissemination. To unravel the role of microRNAs (miRs) during malignancy, we analyzed miR expression in 77 primary breast carcinomas and identified 16 relapse‐associated miRs that correlate with survival and/or distinguish tumor subtypes in different datasets. Among them, miR‐148b, down‐regulated in aggressive breast tumors, was found to be a major coordinator of malignancy. In fact, it is able to oppose various steps of tumor progression when overexpressed in cell lines by influencing invasion, survival to anoikis, extravasation, lung metastasis formation, and chemotherapy response. miR‐148b controls malignancy by coordinating a novel pathway involving over 130 genes and, in particular, it directly targets players of the integrin signaling, such as ITGA5, ROCK1, PIK3CA/p110α, and NRAS, as well as CSF1, a growth factor for stroma cells. Our findings reveal the importance of the identified 16 miRs for disease outcome predictions and suggest a critical role for miR‐148b in the control of breast cancer progression.—Cimino, D., De Pittà, C., Orso, F., Zampini, M., Casara, C., Penna, E., Quaglino, E., Forni, M., Damasco, C., Pinatel, E., Ponzone, R., Romualdi, C., Brisken, C., De Bortoli, M., Biglia, N., Provero, P., Lanfranchi, G., Taverna, D. miR148b is a major coordinator of breast cancer progression in a relapse‐associated microRNA signature by targeting ITGA5, ROCK1, PIK3CA, NRAS, and CSF1. FASEB J. 27, 1223–1235 (2013). www.fasebj.org